Strategi Pembelajaran Dengan Model Pendekatan Pada Peserta Didik Sesuai Capaian Pembelajaran Pada Kurikulum Merdeka - Safaruddin, Safaruddin; Rohadi, Rohadi; Madaniyah, Madaniyah; Mudasir, Mudasir (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study explores the learning strategies aligned with the learning achievements outlined in the Merdeka Curriculum, focusing on the importance of student-centered approaches. The Merdeka Curriculum aims to provide more flexibility in the teaching and learning process, enabling students to engage actively and take responsibility for their own learning. It emphasizes the development of 21st-century skills, such as critical thinking, creativity, collaboration, and problem-solving, which are essential for students' success in the modern world. The research highlights the relevance of teaching models such as Project-Based Learning (PBL) and Problem-Based Learning (PBL) in achieving these learning outcomes, as they encourage students to work collaboratively, think critically, and apply their knowledge to real-life situations. The role of teachers as facilitators, rather than mere transmitters of knowledge, is crucial in this context, as they guide and support students in exploring and mastering subject matter. Moreover, the study emphasizes the need for continuous and holistic assessment, not just to measure academic success but also to evaluate the development of essential skills and attitudes. In conclusion, implementing effective learning strategies in line with the Merdeka Curriculum not only promotes academic achievements but also prepares students for future challenges by fostering independence, creativity, and problem-solving abilities, making them well-equipped for the complexities of the 21st century.